PENGARUH GAYA KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI MELALUI ASPEK KEPUASAN KERJA KARYAWAN DAN KEPERCAYAAN PADA SEKTOR PERBANKAN - Nina Zahra (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
This research refers to the previous research which has done by Chiang and Wang (2012)and also completed by Kalber and Cenker (2007). This research is about “the impact of leadershipstyle on organization commitment mediating by job satisfaction and trust on employed at banksectors”. The background of this research is to know the impact of leadership style on organizationcommitment. The purpose of this research is to examine the impact of leadership style onorganization commitment mediating by job satisfaction and trust. The research is using primarydata by spreading questionnaires to 250 employes of banking sectors in DKI Jakarta, such as:Bank Mandiri, Bank Negara Indonesia, Bank Jabar, Bank Bukopin and Bank Central Asia during2015, however there are 201 questionnaires were returned. The method of data analysis used isStructural Equation Model (SEM). The result of this research concludes that there are positiveimpacts of leadership style on organization commitment mediating by job satisfaction and trust.Keywords: Leadership Style, Job Satisfaction, Trust, Organization Commitment, Banking Sectors.